Great kisses-- and famous lines right out of the movies - Knight, Tim 1963- (Harper Entertainment, 2008)
A tribute to famous romantic scenes from fifty classic movies pairs nostalgic stills with memorable lines of dialogue, including such classics as "The Quiet Man," "Casablanca," and "Roman Holiday."